The Motivation of Media Users and China’s National Media Digitization Construction in the Post-COVID-19 Era - Tan, Yufei; She, Xinlin; Zhou, Cun; Wang, Fangfei (Frontiers in Psychology, 2022)
The sudden impact of COVID-19 has changed social lives. During the epidemic, the authoritative information released by the national media alleviated and released the helplessness and confusion caused by the public’s sense of uncertainty and crisis. When the social structure is facing great challenges, the national media have deep insight into the psychology and internal motivation of media users. With the help of digital media platforms and diversified media technology, it has completed the basic mission of information upload, release, and transmission. It also carries out mutual emotional assistance and comfort for social members through the online aggregation formed by the digital scene transmission of national media. In the post-epidemic era, while the social environment and personal lives gradually return to normal, people are also facing many new situations, and their psychology continues to change. By adapting to the psychological needs of the people in the changing environment and obtaining stable public recognition, support, and use with the help of new ideas and technologies, the national media will build a discourse environment conducive to the destiny of the country and the nation.